Cannabidiol (CBD) Inhibited Rhodamine-123 Efflux in Cultured Vascular Endothelial Cells and Astrocytes Under Hypoxic Conditions - Auzmendi, Jerónimo; Palestro, Pablo; Blachman, Agustín; Gavernet, Luciana; Merelli, Amalia; Talevi, Alan; Calabrese, Graciela Cristina; Ramos, Alberto Javier; Lazarowski, Alberto (Frontiers in Behavioral Neuroscience, 2020)
Rhodamine-123 (Rho-123) is a known tracer dye that can be used to analyze the efflux activity of the ABC-transporter P-glycoprotein (P-gp). In addition, because Rho-123 can be metabolized to Rho-110, then glucuronidated and transported by multidrug resistance-associated protein 2 (MRP2), Rho-123 could also be used to simultaneously monitor the activity of both ABC-transporters P-gp and MRP2. The blood brain barrier (BBB) expresses ABC-transporters P-gp, MRPs and breast cancer resistant protein (BCRP). In refractory epilepsy (RE), these transporters are overexpressed in BBB and BBB-related cells as astrocytes, thus limiting the access of AED to the brain parenchyma. Despite the constant development of new AEDs, approximately 30% of epileptic patients will develop refractory epilepsy (RE). Consequently, the inhibition of these transporters P-gp and MRP2 could help to overcome the pharmacoresistant phenotype. Cannabinoids have been used to treat epilepsy for centuries since ancient times. Recently, different clinical trials and basic studies have shown encouraging results for the use of cannabinoids in RE, though its mechanisms of action are still insufficiently understood. Different stimuli, such as repetitive seizures, status epilepticus and/or hypoxia, can induce overexpression of ABC-transporters, particularly P-gp, in several types of brain cells such as neurons, astrocytes and vascular endothelial cells. Therefore, high levels of P-gp in these cells are commonly found in the brain of both refractory patients and experimental models of RE. We show here that cannabidiol (CBD), a compound that has no psychotropic effects, is capable of inhibiting the efflux of Rho-123 in astrocytes and vascular endothelial cells subjected to hypoxia, in a concentration dependent manner, reaching levels of Rho-123 accumulation similar to those produced by specific inhibitor tariquidar (TQ). Docking studies revealed that CBD could behave as a P-gp substrate by interaction with several residues in the α-helix of the transmembrane domain of P-gp. We conclude that CBD could interact directly with P-gp preventing its functioning although we cannot rule out a trans regulation of P-gp activity. The CBD / P-gp interaction could be at least partially responsible for the success of CBD as an alternative therapy for the treatment of drug-resistant epilepsies.